Gasification Behaviors of Ferrocoke With and Without Water Vapor. Issue 11 (25th September 2022) - Xu, Runsheng; Deng, Shuliang; Zheng, Heng; Huang, Xiaoming; Daghagheleh, Oday; Schenk, Johannes; Zhang, Jianliang; Zhu, Jijian
Abstract : High‐reactivity coke can improve the reaction efficiency in a blast furnace, hence reducing CO2 emission. Herein, traditional coke sample (QM), normal ferrocoke sample (TJ), and modified ferrocoke sample (LQ) are examined. The effect of water vapor on the gasification behaviors and structural evolution of the samples are investigated. Furthermore, the 3D structures of the coke matrix and iron particles are reconstructed by serial sectioning method. The results show that under a pure CO2 atmosphere, the TJ and LQ samples start the gasification reaction earlier than the QM sample. The TJ sample shows the highest reactivity. Under CO2  + H2 O atmosphere, the conversion rate of TJ and LQ samples is slowed. The reoxidation of the metallic iron within the ferrocoke is found for the first time during gasification and causes this phenomenon. Under experimental conditions, when water vapor appears in the atmosphere, the product layer of ferrocoke becomes more porous, and the iron particles have higher possibilities to be oxidized by CO2 . Abstract : The reoxidation of metallic iron within the ferrocoke is found for the first time during gasification. When water vapor appears in the atmosphere, the product layer of ferrocoke becomes more porous, and the iron particles have higher possibilities to be oxidized by CO2 . The oxidation of the reduced iron experiences several stages.